Diagnostic Accuracy of Doppler Ultrasound for Antenatal Detection of Morbidly Adherent Placenta (Journal of Fatima Jinnah Medical University, 2018)
Introduction: The incidence of the morbidly-adherent placenta, previously thought to be very uncommon, is rising in contemporary obstetrical practice and obstetricians must be cognizant of this. Massive obstetric haemorrhage, particularly at delivery, is the principal clinical problem and the condition is associated with a risk of maternal and perinatal mortality of upto 10%. Imaging plays an important role in the antenatal detection of this condition. Objective: To determine the diagnostic accuracy of Doppler ultrasound for antenatal detection of morbidly adherent placenta in patients presenting with placenta previa major degree taking surgical evidence as gold standard. Study Design: Cross sectional study Settings: The study was conducted in Obstetric and gynaecology unit 1, Sir Ganga Ram Hospital Lahore Duration of Study: Jan 2013 to June 2013 Results: Frequency of morbidly adherent placenta is females having placenta previa revealed in 14.38%(n=23),accuracy of Doppler ultrasound for antenatal detection of morbidly adherent placenta in patients presenting with placenta previa major degree taking surgical evidence as gold standard reveals 12.5%(n=3)true positive ,1.25%(n=2) false positive,1.88%(n=3) false negative and 84.38%(n=135) as true negative. Whereas specificity, sensitivity, positive predictive value ,negative predictive value and diagnostic accuracy was calculated as 86.96%,98.54%,90.91%,97.83% and 98.13% respectively. Conclusion: It is concluded that Doppler ultrasound for antenatal detection of morbidly adherent placenta in patients presenting with placenta previa major degree taking surgical evidence as gold standard is an accurate method of diagnosis.
Keywords: Morbidly adherent placenta, diagnosis, ultrasound, diagnostic accuracy.